Circulating short chain fatty acids are associated with depression severity and predict remission from major depressive disorder - Carmen Schiweck; Boushra Dalile; Alice Balliet; Mareike Aichholzer; Helena Reinken; Florian Erhardt; Julius Freiling; Aicha Bouzouina; Carmen Uckermark; Andreas Reif; Kristin Verbeke; Lukas van Oudenhove; et al. (Brain, Behavior, & Immunity - Health, 2025)
Background: Short-chain fatty acids (SCFAs) have been shown to improve depression-like behavior in animal models. However, their predictive value for depression outcomes in humans remains unclear. If SCFAs are predictive, this would provide strong justification for their use in diagnostic and intervention strategies. Therefore, the aim of our study was to determine whether baseline SCFA levels predict remission from depression over a six-month period. Secondary objectives included identifying the SCFA most strongly associated with depression outcomes and assessing the relationship between SCFA levels and inflammatory markers. Methods: A case-control study was conducted, including a pre-selected subset of 50 patients with major depressive disorder (MDD) at baseline, assessed at two time points (25 remitted, 25 non-remitted after six months), and 25 matched healthy controls (CTRL) from a convenience sample. The study was conducted at a university hospital, with fasting SCFA levels measured from high-quality blood samples. Depression severity was assessed using the Montgomery-Åsberg Depression Rating Scale (MADRS), and plasma concentrations of acetate, butyrate, and propionate were measured using gas chromatography-mass spectrometry at baseline and follow-up. Results: At baseline, plasma concentrations of propionate (t(71.2) = −2.38, P = 0.01, Cohen's d = 0.53) and butyrate (t(62.5) = −1.77, P = 0.041, Cohen's d = 0.41) were significantly lower in MDD participants compared to HC. Acetate levels did not differ significantly between groups (t(44.6) = −0.65, P = 0.26, Cohen's d = 0.16). Within the MDD group, baseline butyrate levels were associated with remission at follow-up (β = 2.79 ± 1.41, χ2(1) = 4.29, P = 0.038, OR = 16.3, 95 % CI: 1.01–262.4, AUC ROC = 0.67). Neither acetate (P = 0.43), propionate (P = 0.24), nor C-reactive protein (CRP) (P = 0.83) significantly predicted depression outcomes. Lasso regression identified butyrate as the primary predictor of depression severity at follow-up (β = 2.90 ± 1.39, χ2 = 4.38, P = 0.036). Conclusion: Patients with MDD exhibited lower baseline levels of butyrate and propionate compared to healthy controls. Higher baseline butyrate levels were associated with a greater likelihood of remission at follow-up. These findings suggest that butyrate may play a role in depression recovery, emphasizing the need for future studies to explore the therapeutic potential of butyrate-enhancing interventions in depression treatment.